Social return on investment economic evaluation of supportive care for lung cancer patients in acute care settings in Australia - Amelia Hyatt; Holly Chung; Ruth Aston; Karla Gough; Meinir Krishnasamy (BMC, 2022)
Abstract Background Unmanaged consequences of cancer and its treatment are high among patients with lung cancer and their informal carers, resulting in avoidable healthcare use and financial burden. Provision of cancer supportive care addressing the impacts of cancer and its treatment has demonstrated efficacy in mitigating these consequences; however, globally, there is a lack of investment in these services. Paucity of robust economic evidence regarding benefit of cancer supportive care has limited policy impact and allocation of resources. This study therefore utilised a Social Return on Investment (SROI) methodology to conduct a forecast evaluation of lung cancer supportive care services, to ascertain potential social value and return on investment. Methods An SROI economic evaluation model was developed using qualitative stakeholder consultations synthesised with published evidence to develop the inputs, outcomes and financial value associated with the delivery of a hypothetical model of quality lung cancer supportive care services over a one and five year period. SROI ratios were generated to determine the social value and cost savings associated per every $1AUD invested in cancer supportive care for both the healthcare system and patients. Deadweight, drop off and attribution were calculated, and sensitivity analysis was performed to confirm the stability of the model. Results The value generated from modelled supportive care service investments in a one-year period resulted in an SROI ratio of 1:9; that is, for every dollar invested in supportive care, AUD$9.00 social return is obtained when savings to the healthcare system and benefits to the patients are combined. At five-years, these same investments resulted in greater cumulative value generated for both the patient and the healthcare system, with a SROI ratio of 1:11. Conclusion Our study provides strong evidence for policy makers, clinicians and consumers to advocate for further investment in cancer supportive care, as demonstrated cost savings could be achieved through implementation of the proposed supportive care service model, with these accruing over a five-year period. The SROI model provides a comprehensive framework detailing supportive care services and the health workforce necessary to achieve value-based outcomes for patients and the healthcare system.